Inheritance of signs of «many-flowered» common wheat and evaluation of productivity of the spike of F2 hybrids - V. S. Arbuzova; O. B. Dobrovolskaya; P. Martinek; E. V. Chumanova; T. T. Efremova (Вавиловский журнал генетики и селекции)
Parameters of spike productivity in plants varieties Novosibirskaya 67 (N67), Saratovskaya 29 (S29), Puza-4 and «many-flowered» line Skle 123-09 were assessed in two years with different weather conditions. It was shown that «many-flowered» line Skle 123-09 is significantly higher in the number of grains per spike and number of grains per spikelet than varieties N67, S29 and Puza-4, and that the expression of «many-flowering» depends on the environmental conditions and the genetic background. It was shown that the «many-flowering» is a genetic trait and is therefore workable. A study of hybrids F2 С29×Skle123-09, N67×Skle 123-09, P-4×Skle 123-09 isolated plants with fan-shaped cones and a high number of grains per spikelet as Skle 123-09 and having the best performance of other features as ear varieties recipients. The seeds of these plants will be used to secure «flowering». Two-factor analysis of variance showed that the number of grains per spike knotted depends on growing conditions, genotype and their interaction. Variability of grains per spikelet in drought-resistant varieties of S29 and Puza-4 is mainly dependent on the genotype and, to a lesser extent, on the «genotype×environment» interaction. In variety N67 created for West Siberia, only genotype is a factor. The weight of a grain per ear primarily is primarily affected by «genotype×environment» (almost 60 %), while the influence of «genotype×environmental» was half as strong. The variability of «masse of one grain» in F2 hybrids (S29, P-4×Skle123-09) is influenced by environmental factors, genotype and their interplay. Genotype accounts for the highest impact (> 70 %). F2 hybrids (N67×Skle 123-09) share the greatest variability in the «genotype×environment» interaction (77 %).